Carreira em tecnologia da informação: um estudo junto a profissionais de Minas Gerais - Elida Patricia de Souza (2018)
This thesis aimed to discuss how Information Technology (IT) professionals are building their careers in the current context, in order to suggest a Career Analysis Model in IT. A recent theme, the debate on "careers" has gained even more relevance in an environment in which several and different professional trajectories have been traced by people. With the evolution of the IT field, these professionals have also had a greater range of job possibilities and career development, and with that, they have a lot to say about their specifics and how they deal with work. In this perspective, a descriptive-qualitative research was carried out with 30 IT professionals from the private and public sectors, as well as autonomous and entrepreneurs, who deal with innovation in Minas Gerais. A demographic-functional questionnaire was applied and semi-structured interviews were conducted. These interviews were analyzed from four categories present in the literature of the theme, which are: characterization, development, challenges for the people and challenges for the companies. After initial analysis, these categories were re-evaluated in order to generate an Analysis Model, considering the individual, organizational and contextual aspects of IT careers. The results revealed that the field of IT has evolved and has required professionals to be more active in learning, developing skills and competences, reading and adapting the market in which it operates. It was also noted that learning occurs through formal and informal mechanisms and that certification is not the resource used by the majority of professionals interviewed. With regard to companies, it became evident that the theme of "careers" is not seen as a priority, due to other demands and also the lack of preparation of managers. In addition, the management policies and practices used are not always adapted to the particularities of the IT field. In view of these results, the constructed Analysis Model suggests that in the individual question it is important to consider the moment of choice and / or professional change, the training and posture required, as well as the conditions of the IT profession. Already in the organizational question it was identified that policies and practices are necessary and also associated with IT careers in companies. And, as contextual factors came to the conclusion that economic, political, social and cultural aspects also influence the careers in Information Technology. The development of this research and the IT Careers Analysis Model contributes to the theoretical rescue on the topics "careers" and "information technology", besides providing information that can subsidize the practice of professional choice / replacement, the generation of policies and practices in companies, aimed at the IT public, among others.